Antioxidant and cytotoxicites of Pleurotus eryngii residue polysaccharides obtained by ultrafiltration. (November 2016) - Ma, Gaoxing; Yang, Wenjian; Fang, Yong; Ma, Ning; Pei, Fei; Zhao, Liyan; Hu, Qiuhui
Abstract: Response surface methodology was used to optimize the extraction of polysaccharides Pleurotus eryngii residue (CPPS). The yield of CPPS was 10.69 ± 0.31% under the modified condition (leaching temperature of 70 °C, leaching time of 140 min and ratio of water to raw material of 25 mL/g). Ultrafiltration technology was used for further purification of polysaccharides and two fractions of CPPS-1 and CPPS-2 with different molecular weight ranges were obtained. The antioxidant and cytotoxicities of CPPS-1, CPPS-2 and CPPS were determined in vitro . The results showed that CPPS-1 had the strongest activity. Western blotting results showed that the expression of tumor suppressor p53 and apoptosis activator Bax were up-regulated by CPPS-1 (PEPE-3) fraction while the expression of Bcl-2 was down-regulated. Our results suggested that the antitumor activity of PEPE-3 may be related to its capability in inducing apoptosis via activation of mitochondria apoptosis pathway. Highlights: Pleurotus eryngii residue polysaccharides were obtained using RSM. Two fractions with different molecular weights were obtained by ultrafiltration. The antioxidant and cytotoxicities of CPPS-1, CPPS-2 and CPPS were determined. The antitumor activity of PEPE-3 may via mitochondria apoptosis activation pathway.